1986
DOI: 10.1136/hrt.55.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Relation between coronary anatomy and serial changes in left ventricular function on exercise: a study using first pass radionuclide angiography with gold-195m.

Abstract: SUMMARY Serial changes in left ventricular function on exercise were assessed by first pass radionuclide angiography with gold-195m (half life 30 5 s) in 25 men with known coronary anatomy. In the seven patients with three vessel disease, abnormalities of global left ventricular function and regional wall motion occurred earlier during exercise, were of greater extent at peak exercise, and persisted longer after exercise than in the 11 patients with one and two vessel disease or the seven with normal coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a recent study that assessed the time course of changes in left ventricular function on exercise by rapid sequential first pass radionuclide angiography with gold-195m we found an overall increase in ejection fraction on exercise in patients with normal coronary arteries; however, all the subjects were male. 3 This study has shown that patients with syndrome X are a non-homogeneous group and that in this group women are more likely than men to develop left ventricular dysfunction on exercise. Previous studies have also shown that falls in left ventricular ejection fraction and the development of wall motion abnormalities are associated with a reduced exercise capacity in women,'4 and this is confirmed by the current data.…”
Section: Discussionmentioning
confidence: 89%
“…In a recent study that assessed the time course of changes in left ventricular function on exercise by rapid sequential first pass radionuclide angiography with gold-195m we found an overall increase in ejection fraction on exercise in patients with normal coronary arteries; however, all the subjects were male. 3 This study has shown that patients with syndrome X are a non-homogeneous group and that in this group women are more likely than men to develop left ventricular dysfunction on exercise. Previous studies have also shown that falls in left ventricular ejection fraction and the development of wall motion abnormalities are associated with a reduced exercise capacity in women,'4 and this is confirmed by the current data.…”
Section: Discussionmentioning
confidence: 89%
“…Aliquots of approximately 0.5 mls of gold-195m, with an activity of 550-700 MBq, were introduced into the tubing via the three-way tap, and flushed into the vein using a rapid injection from syringe. Details of the mercury-195m/gold-195m (A.E.R.E., Harwell, England) have been previously described (7) as well as its safety and clinical use in man (8)(9)(10). The studies were performed using a multicrystal gamma camera (Baired Atomic System-77), using a framing interval of 30 msec and a data acquisition time of 30 second.…”
Section: Radionuclide Angiographymentioning
confidence: 99%